Characterization of titanium dioxide nanoparticles modified with polyacrylic acid and H2O2 for use as a novel radiosensitizer. (1st December 2016) - Morita, Kenta; Miyazaki, Serika; Numako, Chiya; Ikeno, Shinya; Sasaki, Ryohei; Nishimura, Yuya; Ogino, Chiaki; Kondo, Akihiko
Abstract: An induction of polyacrylic acid-modified titanium dioxide with hydrogen peroxide nanoparticles (PAA-TiO2 /H2 O2 NPs) to a tumor exerted a therapeutic enhancement of X-ray irradiation in our previous study. To understand the mechanism of the radiosensitizing effect of PAA-TiO2 /H2 O2 NPs, analytical observations that included DLS, FE-SEM, FT-IR, XAFS, and Raman spectrometry were performed. In addition, highly reactive oxygen species (hROS) which PAA-TiO2 /H2 O2 NPs produced with X-ray irradiation were quantified by using a chemiluminescence method and a EPR spin-trapping method. We found that PAA-TiO2 /H2 O2 NPs have almost the same characteristics as PAA-TiO2 . Surprisingly, there were no significant differences in hROS generation. However, the existence of H2 O2 was confirmed in PAA-TiO2 /H2 O2 NPs, because spontaneous hROS production was observed w/o X-ray irradiation. In addition, PAA-TiO2 /H2 O2 NPs had a curious characteristic whereby they absorbed H2 O2 molecules and released them gradually into a liquid phase. Based on these results, the H2 O2 was continuously released from PAA-TiO2 /H2 O2 NPs, and then released H2 O2 assumed to be functioned indirectly as a radiosensitizing factor.